Achieving a low-carbon future through the energy–chemical nexus in China. Issue 12 (26th October 2020) - Li, Yinan; Lan, Song; Pérez-Ramírez, Javier; Wang, Xiaonan
Abstract : The paper proposes the concept of sectoral nexus (energy–chemical nexus) in China for achieving its CO2 emission targets. Abstract : Energy and chemical sectors are the two leading contributors to CO2 emissions in China, with long-term coal-dominated structures. To reach both international and domestic CO2 emission targets and achieve a low-carbon future in China, a closer integration between energy and chemical sectors forming an energy–chemical nexus development pattern is proposed. The energy–chemical nexus for green methanol production is analysed for the first time from a national perspective. It is demonstrated from the perspectives of geography, sectoral development, environment and economic cost that forming an energy–chemical nexus in China for methanol production in 2050 is an attractive and feasible solution. It is also found that the energy–chemical nexus offers solutions to the unique problems in China, such as the unevenly distributed energy supply and demand, high curtailment rate, energy security issue due to lacking natural gas and oil, and domestic CO2 reduction target.